A List of the Caddisflies (Insecta: Trichoptera) from Kyrgyzstan, with a New Record (Triaenodes reuteri McLachlan 1880) - Küçükbasmaci, İbrahým; Canbulat, Savaş (Zootaxa, 2020)
The Trichoptera include more species than any of the other primarily aquatic orders of insects, which are usually found in clean fresh water. Distribution of the species of an order based on geography can provide guidance for researchers working in the field. In the current study, for the first time, a list of known Trichoptera species in Kyrgyzstan is given along with a new record. The list is prepared based on the relevant literature between 1875 and 2020 and a study conducted in 2012. Literature search revealed that 21 known species of caddisflies of 13 genera and 8 families have been reported from Kyrgyzstan; our research found that Triaenodes reuteri McLachlan 1880 is also present in Kyrgyzstan. We also re-illustrate the male genitalia of T. reuteri and provide a detailed redescription. Based on literature search and our observations, the Kyrgyzstan caddisfly fauna has been poorly studied; it is expected that new records and new species will be found in Kyrgyzstan through further research.